Gestión financiera para la obtención y utilización óptima de los recursos financieros de Comercial Castro - Cedeño Sanchez, Agnelio Agustin (2021)
The present investigation was based on the Financial Management for obtaining and optimal use of the financial resources of Importadora Castro, which is dedicated to the retail sale of electrical appliances in specialized establishments: white goods; The main objective of the report is to define a strategic plan that helps in the administration and optimization of financial resources through vertical and horizontal analysis in addition to the application of the respective financial ratios in order to help in the administration and optimization of financial resources. . The strategic plan proposal that was made in the report is aimed at improving the management of the importer, as well as plans and strategies established for the sale of products that they offer. Inventories are financial resources that will be converted into cash later, so their treatment must be careful.